Microtubule modification defects underlie cilium degeneration in cell models of retinitis pigmentosa associated with pre-mRNA splicing factor mutations - Nazlamova, Liliya; Villa Vasquez, Suly Saray; Lord, Jenny; Karthik, Varshini; Cheung, Man-Kim; Lakowski, Jörn; Wheway, Gabrielle (Frontiers in Genetics, 2022)
Retinitis pigmentosa (RP) is the most common cause of hereditary blindness, and may occur in isolation as a non-syndromic condition or alongside other features in a syndromic presentation. Biallelic or monoallelic mutations in one of eight genes encoding pre-mRNA splicing factors are associated with non-syndromic RP. The molecular mechanism of disease remains incompletely understood, limiting opportunities for targeted treatment. Here we use CRISPR and base edited PRPF6 and PRPF31 mutant cell lines, and publicly-available data from human PRPF31+/- patient derived retinal organoids and PRPF31 siRNA-treated organotypic retinal cultures to confirm an enrichment of differential splicing of microtubule, centrosomal, cilium and DNA damage response pathway genes in these cells. We show that genes with microtubule/centrosome/centriole/cilium gene ontology terms are enriched for weak 3’ and 5’ splice sites, and that subtle defects in spliceosome activity predominantly affect efficiency of splicing of these exons. We suggest that the primary defect in PRPF6 or PRPF31 mutant cells is microtubule and centrosomal defects, leading to defects in cilium and mitotic spindle stability, with the latter leading to DNA damage, triggering differential splicing of DNA damage response genes to activate this pathway. Finally, we expand understanding of ‘splicing factor RP’ by investigating the function of TTLL3, one of the most statistically differentially expressed genes in PRPF6 and PRPF31 mutant cells. We identify that TTLL3 is the only tubulin glycylase expressed in the human retina, essential for monoglycylation of microtubules of the cilium, including the retinal photoreceptor cilium, to prevent cilium degeneration and retinal degeneration. Our preliminary data suggest that rescue of tubulin glycylation through overexpression of TTLL3 is sufficient to rescue cilium number in PRPF6 and PRPF31 mutant cells, suggesting that this defect underlies the cellular defect and may represent a potential target for therapeutic intervention in this group of disorders.